Planiculus angulatus, a new species of xyleborine ambrosia beetle from Thailand (Coleoptera, Curculionidae, Scolytinae, Xyleborini) - Sittichaya, Wisut; Cognato, Anthony I. (Zootaxa, 2024)
A new species, Planiculus angulatus sp. nov., is described and P. shiva is reported from Thailand for the first time. A list of Planiculus species found in Thailand with distributions, habitat types and a key to species are also provided.